Terminal deoxynucleotidyltransferase distribution in neoplastic and hematopoietic cells. - Greenwood, M F (1977)
In the present study, terminal deoxynucleotidyltransferase was examined in the peripheral blood and (or) bone marrow of 115 children with a variety of neoplastic, hematologic, and other unrelated disorders. Terminal deoxynucleotidyltransferase activity was present at 4.08+/-0.74 U/108 cells in 23 morphologicall normal bone marrow samples from childhood controls. Terminal transferase was present at greater than 23 U/108 nucleated cells and at greater than31 U/108 blasts in the bone marrow of all children with acute lymphoblastic leukemia studied at initial diagnosis and at disease relapse. Terminal deoxynucleotidyltransferase was detectable at low levels, less than 7.5 U/108 cells, in all remission marrow smaples. Bone marrow terminal transferase activity was markedly elevated in all untreated acute lymphoblastic leukemia patients, whereas low levels which were difficult to interpret were present in the peripheral blood samples of two patients at diagnosis and six patients at relapse who had low absolute lymphoblast counts. Because of greater variation in the lymphoblast content of peripheral blood, bone marrow assays are more reliable in detecting disease activity. Marrow terminal deoxynucleotidyltransferase values obtained during the active phase of acute lymphoblastic leukemia were significantly greater than those found in other types of leukemia, bone marrow malignancies, and hematologic disorders. Terminal transferase determinations in blast cells of two patients with leukemic conversion of non-Hodgkin's lymphoma and in tumor cells from one patient with Burkitt's lymphoma were within the control range. These dat further define the usefulness of terminal deoxynucleotidyltrnasferase assay in the differentiation and classication of hematologic malignancies.